2015
DOI: 10.5194/hess-19-4811-2015
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the ensemble and extended Kalman filters for in situ soil moisture assimilation with contrasting conditions

Abstract: Two data assimilation (DA) methods are compared for their ability to produce an accurate soil moisture analysis using the Météo-France land surface model: (i) SEKF, a simplified extended Kalman filter, which uses a climatological background-error covariance, and (ii) EnSRF, the ensemble square root filter, which uses an ensemble background-error covariance and approximates random rainfall errors stochastically. In situ soil moisture observations at 5 cm depth are assimilated into the surface layer and 30 cm de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 55 publications
3
43
0
Order By: Relevance
“…Previous work by Muñoz Sabater et al (2007) and Fairbairn et al (2015) clearly demonstrated that the assimilation of SSM observations with an SEKF can improve WG2 with the three-layer ISBA-A-gs model. Barbu et al (2014) also demonstrated that the assimilation of LAI reduces phase errors in the modelled LAI evolution.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Previous work by Muñoz Sabater et al (2007) and Fairbairn et al (2015) clearly demonstrated that the assimilation of SSM observations with an SEKF can improve WG2 with the three-layer ISBA-A-gs model. Barbu et al (2014) also demonstrated that the assimilation of LAI reduces phase errors in the modelled LAI evolution.…”
Section: Discussionmentioning
confidence: 88%
“…Draper et al (2009) found the flowdependence from a 24 h assimilation window was sufficient to enable the SEKF to perform similarly to an EKF (which cycles the background-error covariance). Likewise, Muñoz Sabater et al (2007) and Fairbairn et al (2015) found that the SEKF and EnKF performed similarly, in spite of different linear assumptions.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…To estimate RZSM over a large geographical area, many computational techniques have been proposed to retrieve the soil moisture profile using surface information, based on the fact that RZSM is related to surface soil moisture and meteorological forcing through various hydrological processes. Among various alternatives, soil-vegetation-atmosphere transfer (SVAT) models and land surface models (LSMs) are more widely used for large-scale estimation, particularly in combination with data assimilation techniques (Kumar et al, 2009;Xia et al, 2014;Fairbairn et al, 2015). These models use physically based equations to represent the hydrological processes governing RZSM dynamics.…”
Section: Introductionmentioning
confidence: 99%